Drosophila ninaA gene encodes an eye-specific cyclophilin (cyclosporine A binding protein). - Schneuwly, S.; Shortridge, R.D.; Larrivee, D.C.; Ono, T.; Ozaki, M.; Pak, W.L. (Proceedings of the National Academy of Sciences of the United States of America, 1989)
Mutations in the ninaA gene of Drosophila severely reduce the amount of rhodopsin specifically in R1-6 photoreceptors. Isolation of the ninaA gene by chromosomal walking revealed that it is expressed only in the eye and encodes a 237-amino acid polypeptide that shows strong sequence similarity to cyclophilin, a putative molecular target for cyclosporine A, a potent immunosuppressant used in human organ transplantations. Unlike most cyclophilins characterized to date, the ninaA-encoded protein has a putative signal sequence and a transmembrane domain. Each of the three ehtyl methanesulfonate-induced ninaA mutant alleles analyzed shows a single nucleotide change in the mRNA coding region leading to either a nonsense or a missense mutation. We find no evidence that the ninaA-encoded protein is directly involved in phototransduction. The only detectable mutant phenotype that correlates with the severity of molecular defects in the three mutants is the amount of depletion of R1-6 rhodopsin. The above results and the recent findings that cyclophilin is a peptidylprolyl cis-trans-isomerase suggest that the ninaA-encoded protein may be required for proper folding and stability of R1-6 rhodopsin.